Etika Humas Dalam Perspektif Islam : Tinjauan Epistemologis - Fauzan, Fauzan (Tadbir : Jurnal Studi Manajemen Pendidikan, 2018)
In the concept of public relations menejeman required basic and public footing so that what is the goal tecapai from a person or institution that is associated with other parties, community and stakeholders who become the network, the basic concept is what is contained in the basic principles of the Qur'an and hadith, the basic concept is formulated into the principles or principles of public relations and such as how a public relations implemintasi and the basis in the form of action, convey the truth of imformation to other parties, maintain keharmunisan by way of ahklak mulya approach, with the principle of mutualime and there is a balance in getting imformation and accountability in public policy in accordance with what is done by Prophet Muhammad SAW in syiar Islam, so that for the wider society will get the right imformation in accordance with the actual reality. writer in this study multiply some verses of Al-Qur'an and hadith to be the main source of angar in the implementation of public relations that is done more menjujung values and norms in it to encourage the spirit of work high with the intention ihklas solely seek Ridha Allah SWT, this study we deliberately collaborate between historical Prophet Muhammad SAW in membagun city of Mecca and madina as an example of the success of the public relations management done though Prophet Muhammad SAW.serta correlation with muderen reality at this time.